Perhitungan Jumlah Kendaraan Bermotor Di Jalan Pattimura Dan WR.Supratman Kota Pekanbaru - Nadya Dwi Permatasari Vionola; Aryo Sasmita; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Increased motor vehicle activity produces exhaust emissions that cause air pollution,reducing air quality. This research is located at Pattimura and WR.Supratman street as one of collector and local street in Pekanbaru. The purpose of this research is to figure out the amount of vehicle at Pattimura and WR. Supratman street Pekanbaru with recording traffic activities method. The biggest traffic congestion is on Pattimura street which was on monday morning which is had 3944 units. Keywords : Carbon Monoxide Emissions, Vehicle Amount, Speed Of Vehicle